Macrosomia: how accurate are we in detecting it in women with diabetes?. (16th November 2010) - Iliodromiti, S; Naz, A; Lindsay, R; Mackenzie, F
Abstract : Introduction: Royal College of Obstetricians and Gynaecologists guideline No 42 suggests that a caesarean section should be considered for women with diabetes and a fetus with estimated weight >4.5 kg. The authors sought to examine our accuracy in estimating fetal weights (EFW) in women with diabetes. Methods: Fetal weight is estimated in our clinic in all women with diabetes using the Hadlock 1 formula. The authors conducted a prospective, observational study comparing estimated fetal weights at ultrasound to weight at delivery. Results: Over 1 year period, 55 women with diabetes met the inclusion criteria and had available case notes. Fetal weight was estimated 8.6 (SD 4.8) days prior to delivery. The actual and estimated fetal weight were highly correlated (r=0.78, p=0.028). On average estimated fetal weights were 10% (SD 6.3%) lower than birth weight. The difference between estimated and actual weights was not affected significantly by the type of diabetes, maternal body mass index or time between estimation and birth weight. Fetal weight was estimated at >4.5 kg in only one case. In three further cases macrosomia was found at birth (weights 4.57, 4.77 and 4.6 kg) with estimated fetal weights (3.8, 4.3 and 3.7 kg) 15.6% lower, two of which were delivered vaginally and complicated with significant neonatal morbidity. Thus in this small dataset EFW >4.5 kg had a sensitivity of only 25% for detecting macrosomia. Conclusion: The estimated fetal weight in diabetic pregnancies is not accurate enough to predict an adverse outcome. The chance of error is higher in fetuses with a higher birth weight.